Motivation, job satisfaction and service delivery: mid-level staff of Kenneth Dike Library, University of Ibadan, Nigeria (2012)
This is a study on motivation and job satisfaction of mid-level staff in Kenneth Dike Library (KDL), University of Ibadan, Nigeria. Survey method was adopted where responses were elicited through a questionnaire administered on the staff. Answers were sought to questions on staff welfare, satisfaction and productivity. The data collected was analyzed through frequencies, percentages and inferences. It is shown that the morale of staff in the target group was doused due to: frustration resulting from lack of involvement in decision making and inadequate tools and materials with which to work; over-centralization of authority; lack of proper incentives by way of welfare schemes and adequate remunerations. Suggestions are made on the adoption of genuine participatory management style, the introduction of welfare committees to handle staff welfare matters, stringent measures for disciplinary cases plus the fact that government should improve the working conditions of all employees to enhance their level of productivity